The use of pharmacokinetically guided carboplatin chemotherapy in a pre‐term infant with neuroblastoma‐associated spinal cord compression. Issue 9 (28th May 2019) - Hawley, Jessica; Veal, Gareth J.; Errington, Julie; McDonald, Leigh G.; Tweddle, Deborah A.
Abstract: Neonatal neuroblastoma may require chemotherapy either due to mass effect or unfavourable cytogenetics. This case focuses on using pharmacokinetic (PK) guided chemotherapy to treat neonatal neuroblastoma. A newborn baby was noted to have left leg immobility. Imaging showed a retroperitoneal tumour with spinal canal extension causing spinal cord compression. PK‐guided carboplatin was given after conventionally dosed chemotherapy demonstrated no improvement. After initiation of PK therapy, clinical and radiological improvement was seen. We discuss our decision to use PK‐guided chemotherapy despite guidelines recommending weight‐based dosing and discuss the benefits in terms of clinical efficacy without increased toxicity.